2019
DOI: 10.3389/fcell.2019.00160
|View full text |Cite
|
Sign up to set email alerts
|

The Golgin Protein Giantin Regulates Interconnections Between Golgi Stacks

Abstract: Golgins are a family of Golgi-localized long coiled-coil proteins. The major golgin function is thought to be the tethering of vesicles, membranes, and cytoskeletal elements to the Golgi. We previously showed that knockdown of one of the longest golgins, Giantin, altered the glycosylation patterns of cell surfaces and the kinetics of cargo transport, suggesting that Giantin maintains correct glycosylation through slowing down transport within the Golgi. Giantin knockdown also altered the sizes and numbers of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…While we observed the reduction of cisternal length in cells lacking giantin, these authors could not detect significant changes in this Golgi parameter. Moreover, another publication by Satoh et al [120] observed that loss of giantin elongates Golgi cisternae, contradicting their own previous observation [50]. There are several explanations for this discrepancy.…”
Section: Discussionmentioning
confidence: 81%
“…While we observed the reduction of cisternal length in cells lacking giantin, these authors could not detect significant changes in this Golgi parameter. Moreover, another publication by Satoh et al [120] observed that loss of giantin elongates Golgi cisternae, contradicting their own previous observation [50]. There are several explanations for this discrepancy.…”
Section: Discussionmentioning
confidence: 81%
“…In addition to giantin, certain membrane tethering proteins, such as giantin, GRASP55, and GRASP65 ( Figure 3), are thought to regulate the rate of retrograde trafficking, likely to assure efficient recycling of glycosylation enzymes to their target Golgi compartment. RNA interference-mediated depletion of giantin in HeLa cells revealed that this causes aberrant fusion of Golgi cisternae [122]. This, in turn, caused a two-fold increase in the mobility of the glycosylation enzyme ManII as measured by fluorescence recovery after photobleaching and accelerated the trafficking of VSVG to the plasma membrane [123].…”
Section: Golgins Grasps Gorab and Rabsmentioning
confidence: 99%
“…There is no other morphological study yet detailing the expression of Giantin in the epithelial component of gastric carcinoma at the tissue level; however, as the Golgi vesicles suffer fragmentation and morphological changes in cancer cells, it is difficult to interpret if its detection by immunohistochemistry would also point towards a functional protein. Its exact function is not known, and very recently it has been proposed that contrary to the classical view that Giantin would promote trans-vesicle transport of maturing glycol-proteins, it might in fact result in delayed transport between stacks that may enable a correct glycosylation of proteins passing towards the membrane [ 28 ]. It is worth mentioning that none of the above-mentioned studies selected only epithelium for analysis, but rather performed quantitative studies on whole tissue without separating the stroma.…”
Section: Discussionmentioning
confidence: 99%